Development of Interactive Learning Media Based on the Aleis (ATC Licensce Exam Information System) Website for Air Traffic Controllers at Makassar Aviation Polytechnic - Irfan; Hasanah Nur; Ichsan Nadjib (Engineering And Technology Journal, 2024)
The Air Traffic Management study program has graduate learning outcomes level 5 SKKNI flight traffic guides and Aeronautical information lighting, graduate learning outcomes are realized in the issuance of licenses tested by the directorate of flight navigation. The material tested is knowledge related to the field and science. The purpose of the research is to develop interactive learning media with website-based for license exam preparation and explain how to operate the website called "ALEIS" (Air Traffic Controller Licensce Exam Information System). In this study, using R&D (Reseach and Development) research with the development of the Plomp model, the results of validation testing on the application show the usability level value of the "ALEIS" (Air Traffic Controller License Exam Information System) application shows that 96% of the "ALEIS" application makes it easier for users. This is in line with the research objectives, namely developing interactive learning media based on the ALEIS (ATC License Exam Information System) website where the website can be used properly and plays a very important role in preparing for the license exam in the air traffic management program